Peningkatan Kompetensi Pemuda Melalui Pelatihan Multimedia Di Gereja HKBP Rogate Waena Kota Jayapura: Youth Competence Improvement Through Multimedia Training at The HKBP Rogate Waena Church in Jayapura City - Arius A Kambu; Fanny Kristin Tantyah Sitompul; Isma Shalihi Ahlia; Rasi Kasim Samosir; Anggrainy Togi Marito Siregar; Halomoan Hutajulu (Jurnal Pengabdian dan Pengembangan Masyarakat Indonesia, 2026)
This Community Service Program aims to improve the multimedia skills of the HKBP Rogate Waena Church youth in Jayapura City to support creative and adaptive church services in line with technological developments. The activity was carried out in August 2025, involving 40 participants: youth, categorical administrators, and church councils. The implementation methods included material delivery, simulations, and practice in digital content creation and forming a church multimedia team. Evaluation was carried out through pre- and post-test instruments and practice observation sheets. The results showed a significant increase in knowledge, from an average of 82% before training to 100% after training. Practical observations also demonstrated mastery of technical skill with an "excellent" rating in application use, content creativity, and suitability for worship. The outcomes achieved included increased participant knowledge and skills, simple multimedia content products, forming a Church Multimedia Team, and drafting scientific articles. The impact of the activity can be analyzed from four dimensions: strengthening the church organization, increasing youth social participation, optimizing the use of multimedia technology, and academic contributions. Overall, this program is considered adequate and has the potential to be replicated in other churches or communities facing similar challenges